ANALISIS RISIKO INVESTASI PORTOFOLIO SAHAM YANG TERDAFTAR DI BURSA EFEK INDONESIA - AMIN, IQBAL HASYIM (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
The purpose of this study is to see whether the strategy of diversification with the addition of the number of shares on the stock portfolio will lower the level of risk. The portfolio risk level is calculated using the covariant-variance method. Sampling is done by using purposive sampling method with the aim to get the sample according to the purpose of research and from the number of population that exist, then taken sample as many as 25 companies from 5 different sectors. The results of the analysis are as follows: 1) The addition of the number of shares in the portfolio can reduce the level of portfolio risk and if the stock continues to be added then the level of risk reduction will be very small. 2) The right number of shares in forming a portfolio is 20 shares.